Molecular and cellular effects of gestational diet on the developing bovine reproductive and immune systems - Ruiz-Diaz, Maria Dolores (2019)
Protein deficient diets are common in the range beef production system employed in northern Australia. This reflects variation in pasture quality due to local climatic conditions, notably the annual rainy and dry seasons. It is well documented that changes in maternal nutrition during pregnancy can affect the fetal developmental program. The reproductive and immune systems have been demonstrated to be influenced by maternal nutrition; however, much remains unknown. Therefore, the aims of this project were to study the impact of maternal dietary protein intake, mimicking the rainy (14% crude protein dietary content) and the dry (7% crude protein) Australian seasons on the development of the (i) reproductive tract and (ii) immune system of 98 day old bovine fetuses, and on the development of 20 month old bulls. To this end, cows were fed isocalorific high (14%) and low (7%) protein diets during the peri - conception period (60 days prior artificial insemination to 23 days post - conception (dpc)) and then the groups were split into two further groups, half of which remained with the same peri – conception diet, whereas the other half was switched to the opposite diet until 98 dpc (end of the first trimester). This two factorial experimental design provided us with four different dietary groups (low-low, LL; low-high, LH; high-low, HL; and high-high, HH, where low is defined as 7% protein and high as 14% protein), as well as with two different diets per period (LPeri, HPeri, LPost and HPost). The tissues analysed to assess the reproductive tract were the testes in 98 dpc fetuses and the testes and the epididymis in the 20 month old animals. Data pertaining to the fetal testicular cells number, seminiferous tubule abundance and size and blood vessel quantity and size from fetal and adult testis and adult epididymis were collected using a range of histological techniques and statistical analyses. In addition, proteomic analysis of the epididymal fluid extracted from the 20 month old bulls was performed.